Nghiên cứu quá trình hình thành màng phủ kép cromat-vecni bảo vệ chống ăn mòn cho latong-silic - Hùng và cộng sự, Nguyễn Đức (Vietnam Journal of Chemistry, 2014)
Chromate-varnish double films were coated on brass-silica for corrosion protection by storing and using. The result show that the formation process of coating films following three stages are suitable this request.